Application of an integrated behaviour-change model on grandparental adherence towards childhood domestic injury prevention in Hong Kong: a longitudinal study - Martin S Hagger; Patrick Ip; Derwin King Chung Chan; Roni Man Ying Chiu; Catherine M Capio; Patrick S H Yung; Agnes Y K Lai (BMJ Publishing Group, 2024)
Background/purpose Every year, unintentional injury claims thousands of children's lives and causes disabilities in many more. For very young children, these injuries often occur at home. The risks of domestic injury can be reduced through proper implementation of injury preventive measures. In this study, we investigated the motivational and belief processes underlying childhood domestic injury prevention in grandparent caregivers based on the integrated model of self-determination theory and theory of planned behaviour.Method Grandparents (n=299, mean age=62.61 years, SD=5.91, men=20.07%) of 0-2-year-old infants and toddlers self-reported their perceived psychological need support, autonomous motivation, perceived behavioural control (PBC), subjective norms, attitude, intention and adherence with regard to domestic injury prevention for their children at two time points (T1: baseline, T2: 4-month follow-up).Results/outcomes Data were analysed with structural equation modelling, and the proposed model yielded an acceptable fit with the data: χ2=905.09 (df=531), Comparative Fit Index=0.94, Tucker-Lewis Index=0.93, root mean square error of approximation=0.05 and standardised root mean square residual=0.078. Our results supported our hypothesis, demonstrating significant and positive associations between the following key constructs: (1) psychological need support from family and autonomous motivation; (2) autonomous motivation and social-cognitive beliefs; (3) social-cognitive beliefs and intentions; and (4) intention and behavioural adherence. Subjective norms and PBC, but not attitudes, were also found to significantly mediate the indirect effects of psychological need support and autonomous motivation on intention and behavioural adherence.Conclusions Overall, the integrated model seems to be a feasible framework for explaining grandparents' domestic injury prevention behaviour.